2021
DOI: 10.3390/jcm10194485
|View full text |Cite
|
Sign up to set email alerts
|

Cardioplegia between Evolution and Revolution: From Depolarized to Polarized Cardiac Arrest in Adult Cardiac Surgery

Abstract: Despite current advances in perioperative care, intraoperative myocardial protection during cardiac surgery has not kept the same pace. High potassium cardioplegic solutions were introduced in the 1950s, and in the early 1960s they were soon recognized as harmful. Since that time, surgeons have minimized many of the adverse effects by lowering the temperature of the heart, lowering K+ concentration, reducing contact K+ time, changing the vehicle from a crystalloid solution to whole-blood, adding many pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 110 publications
(154 reference statements)
0
11
0
Order By: Relevance
“…It was also found that AQP7 deficiency, protected myocardial cells [22]. The other studies demonstrated that cardioplegic arrest is also strictly related to the altered calcium and potassium ions circuits, and finally, prolonged membrane depolarization [6]. In this study, neonatal rat myoblasts were used as a model of extremely sensitive cells, and ST2C based cardioplegia was used in this in vitro model to estimate cell conditions.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It was also found that AQP7 deficiency, protected myocardial cells [22]. The other studies demonstrated that cardioplegic arrest is also strictly related to the altered calcium and potassium ions circuits, and finally, prolonged membrane depolarization [6]. In this study, neonatal rat myoblasts were used as a model of extremely sensitive cells, and ST2C based cardioplegia was used in this in vitro model to estimate cell conditions.…”
Section: Discussionmentioning
confidence: 91%
“…The high serum concentration of potassium depolarizes the cell membrane suppressing the electric and mechanical activity of cardiomyocytes, causing cardiac arrest [3][4][5]. Cardioplegic solutions can induce cytotoxic effects because of the increased content of potassium ions or its anionic salts [6]; thus, this composition is still improved and developed. There are two types of cardioplegia used in the clinical practice based on the crystalloid solutions (e.g., Btertschneider's formula or St. Thomas' Hospital formula) and so-called blood cardioplegia (one of its components is the patient's blood).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experimental setting, we did not observe any additional benefit of adding adenosine to the warm cardioplegia, as there were no significant differences in the antioxidant enzyme activity among the groups. Further studies should be conducted, as the combination of adenosine with lidocaine and Mg 2+ (known as ALM cardioplegia) has shown promising results as a fully polarizing cardioplegia in human trials [57].…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotective effect of adenosine has long been recognized, and all four adenosine receptors have been implicated. Adenosine is used as an additive in blood cardioplegia to induce a more rapid polarized cardiac arrest via the A1 receptors ( 106 , 107 ). A polarized membrane potential during initial reperfusion may minimize intracellular Ca 2+ overload and reduce cardiac IRI.…”
Section: Effect Of Purinergic Signaling On Irimentioning
confidence: 99%